2008
DOI: 10.1517/17425255.4.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced phototoxicity evoked by inhibition of human ABC transporter ABCG2: development ofin vitrohigh-speed screening systems

Abstract: Background : Photosensitivity depends on both genetic and environmental factors. Pheophorbide a, present in various plant-derived foods and food supplements, can be absorbed by the small intestine. Accumulation of pheophorbide a and porphyrins in the systemic blood circulation can result in phototoxic lesions on light-exposed skin. Objective : As the human ATP-binding cassette (ABC) transporter ABCG2 has been suggested to be critically involved in porphyrin-mediated photosensitivity, we aimed to develop in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 114 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…9,39 Tamura and colleagues proved an in vitro evaluation of photosensitivity risk related to genetic polymorphisms of human ATP-binding cassette (ABC) transporter ABCG and inhibition by drugs demonstrating an inhibition by imatinib on the ATPbinding cassette subfamily G member 2 (ABCG2)-mediated porphyrin transport with a significant enhancement of the cellular photosensitivity. 40,41 We may hypothesize that certain genetic polymorphisms and/or inhibition of ABCG2 by imatinib can enhance the potential risk of photosensitivity. At the same time, imatinib impairs melanogenesis via its inhibition of c-Kit activity, thereby altering the skin's protection against ultraviolet ray exposure.…”
Section: Imatinib Mesylatementioning
confidence: 99%
“…9,39 Tamura and colleagues proved an in vitro evaluation of photosensitivity risk related to genetic polymorphisms of human ATP-binding cassette (ABC) transporter ABCG and inhibition by drugs demonstrating an inhibition by imatinib on the ATPbinding cassette subfamily G member 2 (ABCG2)-mediated porphyrin transport with a significant enhancement of the cellular photosensitivity. 40,41 We may hypothesize that certain genetic polymorphisms and/or inhibition of ABCG2 by imatinib can enhance the potential risk of photosensitivity. At the same time, imatinib impairs melanogenesis via its inhibition of c-Kit activity, thereby altering the skin's protection against ultraviolet ray exposure.…”
Section: Imatinib Mesylatementioning
confidence: 99%
“…This assay takes advantage of the fact that porphyrins have a unique absorption and emission wavelength that makes it amenable to high-throughput screening by fluorescence-activated cell sorting [41]. This screening assay can help not only to identity new Abcg2 inhibitors for therapy but also to eliminate molecules that could lead to disruption of porphyrin homeostasis.…”
Section: Pathologic Implicationsmentioning
confidence: 99%
“…Accumulating evidence suggests that ABCG2 is responsible for the cellular homeostasis of porphyrins and their related compounds 14–16. Hitherto, evidence has been accumulating to show that ABCG2 transports porphyrins in an ATP‐dependent manner 17–19. Furthermore, Robey et al20 reported that ABCG2‐mediated transport of photosensitizers has a potential impact on PDT.…”
Section: Introductionmentioning
confidence: 99%